Efektifitas Konseling Kelompok Pendekatan SFBC untuk Meningkatkan Resiliensi Yatim Piatu di Panti Asuhan Gatot Soebroto Kota Semarang - Karomah, Anggun (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Changes in conditions in an individual's life give rise to various kinds of reactions that have an impact on behavior. Every individual is required to be strong in facing changes, bad support and emotions make the individual unconscious of the strength he has. Therefore, there is a need for methods to increase self-resilience abilities in facing life's stresses and adversities, one of which is group counseling services with a solution focused brief counseling approach. The aim of this research is to find out how to increase resilience in orphaned children in the Gatot Soebroto orphanage, Semarang City. This research is quantitative research using pre-experimental research methods with a One Group Pretest-posttest design. The research population was 15 with 8 research samples. The data collection techniques used were questionnaires and observation with descriptive data analysis methods and t hypothesis testing. The research results show that the effectiveness of the SFBC group counseling approach can increase the resilience of orphans in orphanages with pretest and posttest Sig. 0.000, namely Ha is accepted 0.05 (0.000 < 0.05) and Ho is rejected.